Mathematical modelling of lead assimilation by printing press operators in a poor indoor air quality environment (2008)
Most printing presses in developing countries are located in buildings with inadequate natural and mechanical ventilation such that the press operators work for major hours in poor indoor air quality buildings, which expose them to a wide range of health hazards such as lead poisoning. Understanding how poor air quality affects the operator's body system is studied using a methodology involving the principle of diffusion and the law of mass action. A hypothetical press in Nigeria is used as a case study to illustrate the workability of the model which may be of value to health inspectors to printing presses.